Long-Term Course of COVID-19 Vaccination-Related Headache: A Prospective Multicenter Follow-Up Study - Atalar, Arife Cimen; Acarli, Ayse Nur Ozdag; Baykan, Betul; Bolay, Hayrunnisa; Ertas, Mustafa; Ekizoglu, Esme; Karadas, Omer; Marteletti, Paolo; Polat, Burcu; Gencdal, Isil Yazici; Garcia\\-Azorin, David; Mitsikostas, Dimos; et al. (SAGE PUBLICATIONS LTD, 2023)
International Headache Congress (IHC), Seoul, SOUTH KOREA, SEP 14-17, 2023